Two-dimensional PdSe2-Pd2Se3 junctions can serve as nanowires. (1st June 2018) - Zuluaga, Sebastian; Lin, Junhao; Suenaga, Kazu; Pantelides, Sokrates T
Abstract: While the exfoliation of almost all layered materials results in a monolayer with the same atomic geometry as its bulk counterpart, the exfoliation of PdSe2 results in a monolayer with a different atomic geometry and a new stoichiometry, Pd2 Se3, which is a fusion of two PdSe2 monolayers mediated by Se emission. Here we first report first-principles calculations of lateral junctions between a PdSe2 bilayer and a Pd2 Se3 monolayer. We find that, while several distinct junction geometries are possible, they all exhibit empty interface states below the conduction band. As a result, light n-type doping of either or both sides, e.g. by halogen atoms replacing Se atoms, leads to a remotely-doped interface, i.e. a 1D conducting nanowire that runs along the junction, in between the two semiconductors. We have fabricated such junctions inside a scanning transmission electron microscope (STEM), but doping and transport measurements are not currently practical.